1998
DOI: 10.1017/s0022112098002535
|View full text |Cite
|
Sign up to set email alerts
|

Capillary flow in an interior corner

Abstract: The design of fluids management processes in the low-gravity environment of space requires an accurate description of capillarity-controlled flow in containers. Here we consider the spontaneous redistribution of fluid along an interior corner of a container due to capillary forces. The analytical portion of the work presents an asymptotic formulation in the limit of a slender fluid column, slight surface curvature along the flow direction z, small inertia, and low gravity. The scaling introduced exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
192
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(202 citation statements)
references
References 21 publications
6
192
0
Order By: Relevance
“…Once the MCL reached the pillars ( t = 0.52 s, figure 3b), the excess driving force forced the MCL to accelerate, making the liquid propagate much faster at the interior corner between the pillar and the substrate, known as the Concus-Finn effect (Concus & Finn 1969). In an interior corner with opening angle 2α, the equilibrium velocity could be calculated as U = fU CA = f γ LV /µ (Weislogel & Lichter 1998), where f = sin α(cos θ 0 − sin α)/S is the topological coefficient for capillary flow at the interior corner. θ 0 is the equilibrium contact angle.…”
Section: Multiscale Experimentsmentioning
confidence: 99%
“…Once the MCL reached the pillars ( t = 0.52 s, figure 3b), the excess driving force forced the MCL to accelerate, making the liquid propagate much faster at the interior corner between the pillar and the substrate, known as the Concus-Finn effect (Concus & Finn 1969). In an interior corner with opening angle 2α, the equilibrium velocity could be calculated as U = fU CA = f γ LV /µ (Weislogel & Lichter 1998), where f = sin α(cos θ 0 − sin α)/S is the topological coefficient for capillary flow at the interior corner. θ 0 is the equilibrium contact angle.…”
Section: Multiscale Experimentsmentioning
confidence: 99%
“…Weislogel (1996) found that the capillary flow in V-type interior corner has a constant meniscus height by drop tower experiments, namely initial meniscus height. The capillary flow in an interior corner of rounded wall is numerically simulated using FLOW-3D; the results show that like capillary flow in an interior corner of V-type, the rounded wall also has the initial meniscus height, which is …”
Section: Navier-stokes Equations and Boundary Conditions Of Capillarymentioning
confidence: 93%
“…When the radius of rounded wall R 2 → ∞, the rounded wall transforms to the straight wall, the interior corner transforms to the sharp interior corner, where A is positive and proportional to h 2 (Weislogel 1996). Figure 5 χ,% …”
Section: Navier-stokes Equations and Boundary Conditions Of Capillarymentioning
confidence: 96%
See 2 more Smart Citations